NILAI PENDIDIKAN AKHLAK FILM RUMAH TANPA JENDELA KARYA ADITYA GUMAY DAN PENERAPANNYA DALAM PEMBELAJARAN INTERPRETASI MAKNA TEKS ULASAN DRAMA/FILM DI KELAS XI SMA/SMK - Khabib Sholeh; Dita Anggun Meirani (Universitas Muhammadiyah Semarang, 2017)
This study aims to describe the value of moral education, and its application in learning interpretation of the meaning of the text of drama / movie movie Window House by Aditya Gumay in class XI SMA / SMK. The data were collected by observation method and literature study. The instrument of data collection is done with the help of data and stationery card. Data analysis was done by content analysis method. The result of data analysis is presented by informal technique. From the results of the study concluded that the value of moral education in the film Houses Without Window include morals to himself, which is grateful, sincere, and patient; morals towards his family, that is respect for parents, and love each other towards family members; morals towards each other, that is mutual help, give each other, and love each other. All the values of moral education are established through the structure of story-makers who have aesthetic value and not patronizing. Drama lesson with interpretation material of the meaning of drama / film review text in the film of No Window House in class XI SMA / SMK consists of interpretation understanding, explaining thetext structure of drama / movie. This section contains general or specific descriptions of a drama / film to bereviewed which includes: review objects, prominent / interesting things to review, and staging / screening ofWindows Without Window. Followed by guiding learners to make the film review text, the values contained therein; assigns learners to identify and analyze the intrinsic elements and the value of moral education on the film; guide learners to discuss the results of analysis to peer groups; providing opportunities for learners to report on employment outcomes; and refine the learning outcomes with question and answer method.Keywords: moral education value, drama learning scenario.